2022
DOI: 10.1007/s11102-022-01258-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health and mortality in Cushing’s disease

Abstract: Exposure to cortisol excess in Cushing’s disease (CD) results in increased cardiovascular morbidity and reduces survival, with cardiovascular disease being a leading cause of death. At diagnosis, a significant number of patients have adverse cardiovascular profiles (e.g., obesity, diabetes or impaired glucose tolerance, dyslipidemia, hypertension, cardiac abnormalities and vascular disease). Remission of hypercortisolemia reduces but does not completely eliminate the cardiovascular complications; hazard ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
1
5
0
4
Order By: Relevance
“…The use of novel diagnostic modalities demonstrated that excessive fat accumulation in young and middle-aged patients with CD, already at the early stages of the disease, is associated with some hemodynamic changes in the cardiovascular system, which—at that stage—may still be undetectable in routine assessments. These findings support the need for the early detection of subclinical heart dysfunction in patients with CD to enable early treatment and help prevent cardiovascular complications [ 1 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 70%
“…The use of novel diagnostic modalities demonstrated that excessive fat accumulation in young and middle-aged patients with CD, already at the early stages of the disease, is associated with some hemodynamic changes in the cardiovascular system, which—at that stage—may still be undetectable in routine assessments. These findings support the need for the early detection of subclinical heart dysfunction in patients with CD to enable early treatment and help prevent cardiovascular complications [ 1 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 70%
“…A major challenge in patients with CS is the management of blood pressure [5, 53]. More so it was intriguing that we saw strong effects on endothelia cells and smooth muscle cell abundance, as well as important genes for the vascular system like Vegfa (VEGFA) and VWF (VWF).…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in patients with CS is the management of blood pressure. 12 , 62 More so it was intriguing that we saw strong effects on endothelia cells and smooth muscle cell abundance, as well as on important genes for the vascular system like VEGFA and VWF . It has already been shown that cortisol excess can lead to an increase of thickness in arteries and, therefore, modulate systemic blood pressure and persistent modulation of the vascular system, even after achieving remission of endogenous cortisol excess.…”
Section: Discussionmentioning
confidence: 99%